Are Patient and Surgeon Expectations after ACL Reconstruction Realistic?. Issue 3 (March 2020) - Weekes, Danielle; Campbell, Richard E.; Shi, Weilong J.; Ciccotti, Michael; Salvo, John; Cohen, Steven; Tucker, Bradford; Pepe, Matthew; Freedman, Kevin; Tjoumakaris, Fotios
Abstract: Background: Patient expectations may affect their satisfaction and functional outcomes after treatment of musculoskeletal injuries. Although there is evidence that patient expectations of ACL reconstruction (ACLR) are inflated, there is limited knowledge about the relationship between physician and patient expectations and patient outcomes after they completely recover from ACLR. Furthermore, it is unclear if specific patient factors influence these expectations. Questions/purposes: (1) Are patient and surgeon expectations of knee function 18 months after ACLR similar? (2) Are patients' and surgeons' expectations of outcomes similar to patients' actual 2-year outcomes? (3) Is there a relationship between preoperative or intraoperative parameters and expectations? (4) Is there a relationship between preoperative or intraoperative parameters and 2-year ACLR outcomes? Methods: One-hundred twenty-nine patients undergoing primary ACLR were prospectively enrolled in this study, with 98 (76%) completing 2-year follow-up. Patients completed the IKDC Subjective Knee Evaluation preoperatively and at 3, 6, 12, and 24 months postoperatively. Patients also completed the same questionnaires preoperatively to evaluate expected knee function 18 months after surgery. Immediately postoperatively, surgeons completed the same questionnaires regarding the expected postoperative outcome at 18 months postoperative. Preoperative and intraoperative data were collected to determine an association between expectations and outcomes. Nonparametric analysis was performed using the Mann-Whitney U test, the paired Wilcoxon signed ranks tests and Spearman's correlations, as applicable. Results: There was no difference between patient and surgeon expectations (patient, 94.8 [range 47.4-100] versus surgeon, 94.3 [range 46-100]; p = 0.283), and there was no correlation between higher patient expectations and higher surgeon expectations (r = 0.168, p = 0.078). Patient and surgeon expectations were greater than the actual postoperative outcomes (2-year postoperative: 89.7 [range 32.2 to 100]; p < 0.0001); however, the differences are unlikely to be perceived. There was no correlation between higher 2-year postoperative outcomes and higher patient expectations (r = 0.14, p = 0.186) or higher surgeon expectations (r = 0.019, p = 0.86). Arthroscopic evidence of cartilage damage was independently associated with the worst patient and surgeon expectations. The surgeons themselves were also independently associated with surgeon expectation (p < 0.001). No parameters were associated with postoperative outcomes. Conclusions: There are no clinically significant differences between surgeon expectations, patient expectations, and 2-year actual outcomes. However, there is also no correlation between the patient expectations, surgeon expectations, and actual outcomes. Although expectations are similar to actual outcomes for most patients, surgeons are unable to accurately predict outcomes for specific patients; thus, preventing adequate patient counseling. Surgeons should be cautious when evaluating and counseling patients preoperatively and avoid assuming high expectations. Level of Evidence: Level II, therapeutic study.